A Review of Bioinformatics for Primatologists: A Note for Reducing Living Primate Model and Supporting the Conservation - Al Hakim, Rosyid Ridlo; Nasution, Erie; Rukayah, Siti; Putri, Esa; Riani, Sri (Journal of Advanced Health Informatics Research, 2023)
The problem is that bioinformatics, as a part of health informatics, plays a role in studying molecular things and genetic studies. Primatologists who studied primates, as well as non-human primates (NHPs), found a dilemma relating to biomedical studies and conservation. Which one to achieve, the goal of being a model animal or their conservation efforts, of course, has very few boundaries. The solution in this study tries to review how to seek to reduce the quantity of NHPs model animals but not reduce their quality, on the other hand, considerations of conservation efforts. The research contribution in this paper proposed authors' perspectives according to the context of the NHPs model as well as conservation efforts, which are considered for dry or wet materials, which means that the genetic resources come. This study would give the 3Rs principle idea, reducing, which contributes to its conservation efforts. This review method used literature surf, scientific selection, and report writing. The result proposed the discussion about related scientific sources as well as the authors' perspective to solve the problem of animal model uses in NHPs. The conclusion is that NHPs are fortunate to receive special attention outside their studies as animal models, even though they are still used in research to benefit humans. Of course, the benefits and drawbacks of using genetic samples—whether wet or dry—are only relevant when used as research materials for medical and bioinformatics investigations. So that there are no more instances of increasing conservation status brought on by the volume of research on the use of model animals, efforts to conserve NHPs as a component of wildlife in nature must be considered.